IMPLEMENTATION OF INDEPENDENT CURRICULUM IN IMPROVING QUALITY OF LEARNING IN ELEMENTARY SCHOOLS - Rina Purwantini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Infrastructure and technology limitations, teacher readiness and competence , parent and community participation, evaluation and assessment, and resistance to change are some of the obstacles faced in implementing the independent curriculum. The purpose of this study is to determine how the implementation of the independent curriculum improves the quality of learning in elementary schools. This research uses a qualitative research method with a literature study approach. Data sources consist of national and international scientific journals. The data collection process comes from Scopus and Google Scholar focusing on literature from relevant journals, which are related to the implementation of the independent curriculum in improving the quality of learning in elementary schools. Data analysis focuses on the implementation of the curriculum from various references. The results of this study indicate that there is a very large influence between the openness of teachers and related parties in determining a curriculum planning, so that in its implementation it is in accordance with the conditions of students, educational goals and must be adjusted to the student's environment.